The Sonnet - Regan, Stephen 1957- (Oxford Oxford University Press, 2019)
The Sonnet provides a comprehensive study of one of the oldest and most popular forms of poetry, widely used by Shakespeare, Milton and Wordsworth, and still used today by poets such as Seamus Heaney, Tony Harrison and Carol Ann Duffy. This book traces the development of the sonnet from its origins in medieval Italy to its widespread acceptance in modern Britain, Ireland and America. It shows how the sonnet emerges from the aristocratic courtly centres of Renaissance Europe and gradually becomes the chosen form of radical political poets such as Milton. The book draws on detailed critical analysis of some of the best-known sonnets written in English to explain how the sonnet functions as a poetic form, and it argues that the flexibility and versatility of the sonnet have given it a special place in literary history and tradition.
Includes bibliographical references (pages viii-xi, 403-417) and index.
Keywords: Sonnet